Factors Associated with Variations in Home Blood Pressure Monitoring among Adults with Hypertension: Systematic Review - Okubai, Tecleab; Kahsay, Desale Tewelde; Netsereab, Tesfit Brhane; Asnake, Melat Adugna (SAGE Publications, 2026)
Introduction
Home blood pressure monitoring is often considered less reliable than conventional blood pressure monitoring due to different factors.
Aim
To investigate variations in home blood pressure monitoring and associated factors, differences in measured blood pressure under varying conditions such as postural changes from sitting to standing, among adults with hypertension.
Methods
A systematic review of studies was conducted on adults (≥18 years) with hypertension. Peer-reviewed studies published between 1992 and 2025 were searched in the Web of Science, PubMed, MEDLINE, and CINAHL databases in August 2023 and September 2025. The review included studies on home blood pressure monitoring, the associated factors, and reported in systolic and/or diastolic values. The main outcome was variations in home blood pressure monitoring categorized as small (<5 mmHg), moderate (5–15 mmHg), or large (>15 mmHg). Associated factors were also identified and the findings were analyzed using narrative synthesis.
Results
A total of 2,843 peer-reviewed articles were identified across four databases, of which 33 met the inclusion criteria. Generally, variations in home blood pressure monitoring ranged from −21.8 to +9.5 mmHg for systolic blood pressure and from −5.0 to +5.5 mmHg for diastolic blood pressure, where the + and − signs indicate the direction of changes. Fifteen factors associated with variations in home blood pressure monitoring were identified and broadly categorized into patient, device, procedural, protocol, and observer factors with related subcategories.
Conclusions
There were variations in home blood pressure monitoring and were associated with the factors, ranging from large decreases to large increases in both systolic and diastolic blood pressures, among adults with hypertension. Therefore, when measuring and interpreting blood pressure at home, it is essential to consider the factors associated with the variations. Furthermore, this study serves as a baseline for future research. This review is registered in PROSPERO.